Inhabiting “no places”: Subjectivity and family abilities for confronting a socio-natural disaster in Chile - Luisa Rojas-Páez; José Sebastián Sandoval-Día (Íconos)
The following work analyzes the subjective dimension of vulnerability-ability of families that have been displaced by an earthquake in Chile. A qualitative design was selected, which included a theoretical sample, ten female heads of household and three institutional agents linked to the displacement and reconstruction of homes after the disaster. The data is produced by episodic interviews that use coding as an analytical strategy based on the grounded theory. The first result shows differences in the meanings assigned to displacement by the institutions that respond to disasters and the relocated families. At the institutional level, the predominant perspective was one based on instrumental reasoning about inhabiting, which reduced this concept to the facilitation of survival and the mere topographical occupation of a physical-material space. Meanwhile, for the relocated families, living in a camp meant an intensification of an “experience of continual vulnerability”, which signified they were in a “no place” of circumstantial transit. As part of the second results, four family abilities were identified that did not subvert the social and structural vulnerability present but did enable the emergence of four configurations of tactics of agency and resistance in confronting disasters: resignation, individualism, concealment and solidarity. The conclusions highlight the importance of integrating a sub-jective dimension of vulnerability-ability in confronting the process of environmental displacement in order to guide the processes of relocation and psycho-social interventions sustained in a multidimensional perspective of inhabiting.